2014
DOI: 10.1080/19382014.2015.1006075
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of HIF-2α in pancreatic β cells does not alter glucose homeostasis

Abstract: Keywords: Hypoxia inducible factor b cell glucose homeostasis diabetes mellitus pancreas Abbreviations: ARNT, aryl hydrocarbon receptor nuclear translocator; EPAS1, endothelial PAS domain protein 1; GLUT1 glucose transporter 1; GTT, glucose tolerance test; HFD, high fat diet; HIF, hypoxia inducible factor; HIF-1a, hypoxia inducible factor-1 a; HIF-1b, hypoxia inducible factor-1 b; HIF-2a, hypoxia inducible factor-2 a; i.p., intraperitoneal; ITT, insulin tolerance test; OE, overexpression; VEGF, vascular endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…These observations suggest that HIF-2α activity has no major role in the pancreatic islet’s response to either cellular or environmental hypoxia. Furthermore, previous studies showed that, in contrast to HIF-1α ( 23 ), overexpression of HIF-2α in β cells has no impact on glucose homeostasis ( 32 ). To ensure the absence of any negative impact of PX-478 on cell viability, we performed propidium iodide staining, which confirmed that, regardless of GKA50 cotreatment, treatment with PX-478 did not lead to an increase in cell death (fig.…”
Section: Resultsmentioning
confidence: 99%
“…These observations suggest that HIF-2α activity has no major role in the pancreatic islet’s response to either cellular or environmental hypoxia. Furthermore, previous studies showed that, in contrast to HIF-1α ( 23 ), overexpression of HIF-2α in β cells has no impact on glucose homeostasis ( 32 ). To ensure the absence of any negative impact of PX-478 on cell viability, we performed propidium iodide staining, which confirmed that, regardless of GKA50 cotreatment, treatment with PX-478 did not lead to an increase in cell death (fig.…”
Section: Resultsmentioning
confidence: 99%
“…Brunt et al suggested that overexpression of HIF-2α does not alter glucose homeostasis in pancreatic β cells. 177 However, recent studies have described a critical role of HIF-2α in hepatic glucose homeostasis. 178,179 Taniguchi et al uncovered that the increased hepatic HIF-2α, but not HIF-1α, improves glucose tolerance and insulin sensitivity to ameliorate diabetes.…”
Section: Hypoxia Signaling In Human Diseases Metabolic Diseasesmentioning
confidence: 99%